Physiological and Immunomodulatory Effects of Purslane Extract in Cirrhinus mrigala Juveniles: Implications for Sustainable Production - Muhammad Faisal; Syed Makhdoom Hussain; Shafaqat Ali; Dariusz Kucharczyk; Khalid A. Al-Ghanim (Animals)
Medicinal plants are rich in nutrients and bioactive compounds, making them potentially suitable for use as chemotherapeutic agents and as additives in aquafeed. Our research evaluated the effects of purslane (Portulaca oleracea) extract supplemented in sunflower-based diets on the growth, carcass composition, blood indices, mineral content, liver antioxidant enzyme profile, and immune response in Cirrhinus mrigala (8.26 ± 0.07 g/fish). The juveniles were fed one of seven different diets—T0 (no extract), T1 (0.5%), T2 (1%), T3 (1.5%), T4 (2%), T5 (2.5%), and T6 (3%)—twice daily, at a feeding rate of 5% of their live body weight. They were stocked in V-shaped steel tanks for 90 days, with 15 juveniles per tank and three replicates per dietary treatment. The results of this research revealed that 1–2% purslane extract substantially enhanced growth indices in fish (p < 0.05). Furthermore, the supplementation of 1–2% dietary purslane extract in the diet significantly lowered fat content and improved protein content (p < 0.05) compared to the diets with 0% and 3% purslane extract inclusion. The outcomes also indicated that the hematology and mineral content in the bodies of juveniles were significantly improved (p < 0.05) at all levels of purslane supplementation, relative to the control groups with 0% and 3% inclusion levels. Moreover, the administration of purslane extract markedly increased the liver antioxidant profile, including glutathione peroxidase, superoxide dismutase, and catalase. Additionally, there was a notable reduction in malondialdehyde levels when fish were fed diets having 1% and 1.5% extract. The findings of this study also revealed improvements in immunological markers, characterized by increased lysozyme activity and elevated total globulin levels. The current research suggests that supplementing C. mrigala diets with 1% purslane extract optimally enhances growth and immunity.